Ermittlung der Wasser-Energiedosis nach der Sondenmethode gemäß DIN 6800 Teil 1: Vorschlag für eine Erweiterung der Grundgleichung - Hartmann, Günther H.; Hensley, Frank W.; Kapsch, Ralf-Peter; Poppe, Björn; Sauer, Otto; Wuerfel, Jan; Zink, Klemens (Zeitschrift für medizinische Physik, 2020)
For any detector to be used for the determination of absorbed dose at the point of measurement in water a basic equation is required to convert the reading of the detector into absorbed dose in water. The German DIN 6800 part 1 provides a general formalism for that. A further differentiated formalism applicable to photon dosimetry is suggested in this work. This modified formalism presents the two following still general and at the same time fundamental properties of any dosimetry detector: a) a clear distinction of correction factors with respect to the physical processes involved during the measurement, and b) the fact that the process of energy absorption in the detector is determined by the spectral distribution of the fluence of the secondary charged particles. It is concluded that based on the modified formalism and knowing this spectral distribution within the detector a general method is available with benefits for ionization chambers as well as for any other dosimetry detector and which is applicable at reference as well as non-reference conditions without any preconditions.
Available online: 2 October 2019
Gesehen am 08.07.2020